2004
DOI: 10.1029/2003jd004326
|View full text |Cite
|
Sign up to set email alerts
|

Fluxes of nitrogen oxides over a temperate deciduous forest

Abstract: [1] Eddy covariance flux measurements of NO, NO 2 , and O 3 were obtained above the mixed deciduous canopy at Harvard Forest in central Massachusetts from April to November 2000. Net deposition of NO x was observed throughout the measurement period, with average velocity of $0.2 cm s À1 . At night, NO 2 is deposited at a rate that depends nonlinearly on NO 2 concentration and cannot be explained by N 2 O 5 hydrolysis, suggesting HONO formation by heterogeneous disproportionation of NO 2 . During the day, photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 35 publications
5
98
1
Order By: Relevance
“…McCalley and Sparks (2009), for example, report on 86 % for NH 3 measured with their converter system and 100 % for NO 2 . Horii et al (2004) compared concentrations of NO 2 obtained by TDLAS versus photolysis-chemiluminescence instruments and found a slope of 1.1 ± 0.2 with a R 2 of 0.91. The TD-LIF instrument presented by Farmer et al (2006) was tested by Thornton et al (2003) and Rosen et al (2004) with a conversion efficiency of >95 % for NO 2 and >94 % for PN using photolysis-chemiluminescence and gas chromatographs equipped with electron capture detectors, respectively, for comparative measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…McCalley and Sparks (2009), for example, report on 86 % for NH 3 measured with their converter system and 100 % for NO 2 . Horii et al (2004) compared concentrations of NO 2 obtained by TDLAS versus photolysis-chemiluminescence instruments and found a slope of 1.1 ± 0.2 with a R 2 of 0.91. The TD-LIF instrument presented by Farmer et al (2006) was tested by Thornton et al (2003) and Rosen et al (2004) with a conversion efficiency of >95 % for NO 2 and >94 % for PN using photolysis-chemiluminescence and gas chromatographs equipped with electron capture detectors, respectively, for comparative measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Shaw et al, 1998). Further problems in measuring N r compounds are the lack of capable techniques for fastresponse detection, issues regarding inlet design, sampling losses and air column chemical reactions for highly reactive and soluble N r species (Horii et al, 2004(Horii et al, , 2006. Hence, the establishment of large-scale dry deposition monitoring networks of total N r remains nearly impracticable.…”
Section: Exchange Measurements Of Reactive Nitrogen Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emissions of NO from soils at HFEMS are negligible (Horii et al, 2005). But Horii et al (2004) observed bi-directional fluxes of NO 2 and suggested a compensation point for NO 2 near 1.5 ppbv at HFEMS, the ambient concentration below which NO 2 is emitted from stomata. Given that [NO 2 ] approached this level occasionally during the daytime within the selected period (Fig.…”
Section: Evaluation Of Modeled V D (No Y )mentioning
confidence: 99%
“…EC flux measurements of NO y , NO, and NO 2 fluxes have been reported (e.g. Delany et al, 1986, Horii et al, 2004Munger et al, 1996;Rummel et al, 2002). Most other studies of N fluxes have used enclosure or indirect estimation techniques, including gradient measurements or resistance modeling (Hanson and Lindberg, 1991;Wesely and Hicks, 2000).…”
Section: Introductionmentioning
confidence: 99%